My first look at touch. - Random House (Firm) (New York : Random House, 1990)
Labeled pictures depict things one can touch that are wet, rough, soft, smooth, furry, prickly, squishy, and sticky.
School Library Journal
K-3
Keywords: Touch -- Juvenile literature; Touch -- Pictorial works; Senses and sensation -- Pictorial works; Touch; Senses and sensation